Linking systems thinking with citizenship education at the university (2024)
Researchers from different disciplines have advocated for the incorporation of Systems Thinking in higher education in various fields such as environmental studies, engineering, economics and management. Nevertheless, educational experiences that seek to integrate the systems approach and citizenship education are not numerous and have not been sufficiently documented. This research paper presents classroom research aimed at understanding how Systems Thinking and citizenship education are articulated within a general education course. Design/methodology/approach: The research was designed using Grounded Theory within an exploratory-descriptive approach. To collect data, the following techniques were used: participant observation, focus group and documentary analysis. The data analysis was carried out through the constant comparative method in its open, axial, selective and theoretical contrast coding phases. Findings: The data analysis highlights the potential of Systems Thinking within the context of Citizenship Education as a comprehensive set of cognitive, affective and methodological tools. Moreover, it sheds light on the pedagogical practices, the teaching strategies and the type of socioemotional interactions in the classroom that are key elements in promoting citizenship attitudes, ideas and behaviors. Originality/value: The research underscores the importance of a systemic vision of education that explicitly incorporates social-emotional learning and experiences of citizen participation beyond the classroom where students can build new knowledge from first-hand interactions with processes of social transformation.